2022
DOI: 10.1002/rra.3946
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐automated hydraulic model wrapper to support stakeholder evaluation: A floodplain reconnection study using 2D hydrologic engineering center's river analysis system

Abstract: Floodplain reconnection projects are largely nature-based solutions that have great potential to restore channel stability, attenuate stormwater, improve flood resilience, and improve water quality. The suite of possible restoration options for a given study area must consider the multiple uses and functions of river corridors, along with the potential impacts and benefits to adjacent infrastructure. Therefore, decision-support frameworks designed to help stakeholders compare floodplain reconnection scenarios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…In the study area, floodplain restoration for floodwater, sediment, or nutrient storage would likely be most effective downstream of reach M17 (greater than approximately 90 km 2 of drainage area). Reaches (i.e., M05, M19A, M19B, and M20; see Supplemental S.9) with SSP‐flow curves that exceed critical SSP Thresholds at small design floods such as the Q5 (e.g., Figure 6, Note 1), may be good choices for restoration projects either at the reach itself or in upstream reaches to attenuate peak flows and dissipate flood energy and erosion/incision hazard (Gourevitch et al, 2020; Morris et al, 2005; Rijke et al, 2012). Reaches (i.e., M06, M08, M11, M13, and M15) that have large DSVC accessed at small design floods or have CSVC accessed only at moderate design floods (Figure 6, Note 2) may be good choices for channel reconnection (e.g., berm lowering or removal; installation of cross‐culverts beneath roads) (Morris et al, 2005; Worley et al, 2022). Reaches with large CSVC that can be accessed at small design floods (i.e., M05, M08, M10, M11, M12, and M16) may be most suitable for conservation easements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the study area, floodplain restoration for floodwater, sediment, or nutrient storage would likely be most effective downstream of reach M17 (greater than approximately 90 km 2 of drainage area). Reaches (i.e., M05, M19A, M19B, and M20; see Supplemental S.9) with SSP‐flow curves that exceed critical SSP Thresholds at small design floods such as the Q5 (e.g., Figure 6, Note 1), may be good choices for restoration projects either at the reach itself or in upstream reaches to attenuate peak flows and dissipate flood energy and erosion/incision hazard (Gourevitch et al, 2020; Morris et al, 2005; Rijke et al, 2012). Reaches (i.e., M06, M08, M11, M13, and M15) that have large DSVC accessed at small design floods or have CSVC accessed only at moderate design floods (Figure 6, Note 2) may be good choices for channel reconnection (e.g., berm lowering or removal; installation of cross‐culverts beneath roads) (Morris et al, 2005; Worley et al, 2022). Reaches with large CSVC that can be accessed at small design floods (i.e., M05, M08, M10, M11, M12, and M16) may be most suitable for conservation easements.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate our framework, we chose the Mad River watershed located in central Vermont (Figure 1), due to the abundance of prior work related to stream geomorphic conditions and processes (Ross et al, 2019; Worley et al, 2023) and the availability of a well‐calibrated 2D HEC‐RAS model for assessing our low‐complexity model results (Seigel, 2021; Worley et al, 2022). Elevations in the Mad River watershed range from 132 to 1245 m above sea level.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These variations reflect the moderating influence of factors such as event magnitude (e.g., Garcia‐Ruiz et al, 2010; Cruise et al, 2010) the scale of landscape change or intervention (e.g., Škute et al, 2008; Ward et al, 2008), vegetation characteristics (e.g., species; Fahey & Jackson, 1997; Murphy et al, 2021 and maturity; Viola et al, 2014), antecedent conditions such as soil moisture (e.g., Ghimire et al, 2013; Hughes et al, 2020), catchment size (e.g., Deutscher and Kupec, 2014) and legacy effects associated with the landscape history (e.g., Ahiablame et al, 2019). Only 3% of high flow studies showed no change or negligible change, attributed to physical characteristics at the catchment scale (O'Donnell et al, 2011) and site or valley scale (Worley et al, 2022). Interactions between multiple environmental factors created a combination of increases and decreases in flood risk for some publications: 11% reported variable outcomes spanning attenuation and increased peak flows within the same study.…”
Section: Trends and Gaps In Hydrological Research On Rewildingmentioning
confidence: 99%